2016
DOI: 10.1515/boca-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked enzyme aggregates (CLEA) in enzyme improvement – a review

Abstract: Structural and functional catalytic characteristics of cross-linked enzyme aggregates (CLEA) are reviewed. Firstly, advantages of enzyme immobilization and existing types of immobilization are described. Then, a wide description of the factors that modify CLEA activity, selectivity and stability is presented. Nowadays CLEA offers an economic, simple and easy tool to reuse biocatalysts, improving their catalytic properties and stability. This immobilization methodology has been widely and satisfactorily tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 61 publications
2
83
0
8
Order By: Relevance
“…In actual applications, PGA was presented in an immobilized form in order to improve the recyclability and reusability. PGA could be immobilized by adsorption method, cross‐linking method, and covalent bonding method . Among them, covalent binding method was favored by researchers due to strong binding force between PGA and target, abundant types of functional groups available for design, high utilization ratio, and so on …”
Section: Introductionmentioning
confidence: 99%
“…In actual applications, PGA was presented in an immobilized form in order to improve the recyclability and reusability. PGA could be immobilized by adsorption method, cross‐linking method, and covalent bonding method . Among them, covalent binding method was favored by researchers due to strong binding force between PGA and target, abundant types of functional groups available for design, high utilization ratio, and so on …”
Section: Introductionmentioning
confidence: 99%
“…Among the disadvantages of the method are its low mechanical stability and the unfortunate lack of exact methodologies for the synthesis of crosslinked enzymes that allow the size, selectivity and stability of the enzymes to be controlled. Hence, each step in the process must be carefully designed for each enzyme and thus requires a great effort for its synthesis and implementation . Additionally, the implementation of the method usually requires the use of glutaraldehyde, which is a toxic substance .…”
Section: Polymer Supports For Degradation Of Organic Pollutantsmentioning
confidence: 99%
“…Hence, each step in the process must be carefully designed for each enzyme and thus requires a great effort for its synthesis and implementation . Additionally, the implementation of the method usually requires the use of glutaraldehyde, which is a toxic substance . To solve this problem, recent studies have focused on the replacement of glutaraldehyde by nontoxic molecules, such as maltose, lactose and sucralose, to obtain good conservation of activity in the immobilized enzymes …”
Section: Polymer Supports For Degradation Of Organic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Despite their popularity, CLEAs exhibit inherent drawbacks associated with mass-transfer limitations, 27,30,31 mild physical resistance, especially in aqueous media, 27 inactivation caused by the cross-linking reaction of GA with critical residues of the enzyme, 20,32 and poor cross-linking capacity in enzymes with reduced external lysine residues. [33][34][35] To overcome these matters, several authors have found interesting alternatives, as the use of other reagents (polyethylenimine [PEI], 32 dextran polyaldehyde 36 or chitosan 37 ), the enzymatic amination with PEI or polymers to later cross-link with GA and the use of a co-feeder (proteins or polymers) to increase the lysine residues or amino groups for subsequent cross-linking. 35,[38][39][40] In the case of CALB, the cross-linking reaction with GA is hampered by the reduced number of lysine residues available in its structure.…”
mentioning
confidence: 99%